EXAMINING THE INFLUENCE OF PERCEIVED RISK AND USER-FRIENDLINESS ON THE USAGE INTENTION OF QRIS IN BERSEHATI TRADITIONAL MARKET - Koloay, Kesia Sheren Prillya; Worang, Frederik G.; Gunawan, Emilia Margareth (Universitas Sam Ratulangi, 2024)
The adoption of digital payment systems, such as QRIS (Quick Response Code Indonesian Standard), is becoming increasingly relevant in this modern era. However, there is a notable lack of research focusing specifically on the adoption of these systems within traditional settings. Thus, this thesis addresses this gap by Examining the Influence of Perceived Risk and User-Friendliness on the Usage Intention of QRIS in Bersehati Traditional Market, the largest traditional market in Manado. Involving 100 respondents, the research uses the Purposive Sampling Technique and analyzes using SPSS 29 software. The findings reveal that both Perceived Risk and User-Friendliness influence the intention to use QRIS. However, User-Friendliness has a greater influence on usage intention compared to Perceived Risk. These results underscore the importance of addressing perceived risks and enhancing user-friendliness as key strategies in promoting the widespread adoption of QRIS as a digital payment system. Keywords: Perceived Risk, User-Friendliness, Usage Intention, QRIS, Digital Payment Systems